Analisis Kebutuhan Bahan Slice Fruit Untuk Buffet Lunch Di Cold Kitchen Hotel Morazen Surabaya - Kholifatin Nur Faiza; Niken Purwidiani; Ita Fatkhur Romadhoni; Lucia Tri Pangesthi (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
The hospitality industry is widely used as a place to carry out various events. One of them is the Morazen Surabaya hotel which is used as a venue for various events such as meetings, birthdays, weddings, engagements, and others. One of the dessert menus in the lunch buffet is sliced fruit. This study aims to find out the procedure in the analysis of slice fruit material needs and the analysis of material needs in the Morazen Surabaya hotel in accordance with the standards. This research was carried out in August – December 2023. The stage of implementing the research includes title identification, preparation of research instruments, data collection, data processing, and data presentation. This study uses a qualitative descriptive method with data collection techniques carried out using direct observation, interviews through instrument sheets through instrument validation and documentation in the form of tables, drawings and documentation during interviews. The data analysis used is an interactive model according to Milles and Huberman with data validity tests. The results of this study show the flow of analysis of the need for slice fruit ingredients and the calculation of the need for slice fruit ingredients in accordance with the revenue provided. Slice fruit is a dessert interlude menu that has a lot of interest for buffet lunch guests. How to analyze and calculate the need for slice fruit ingredients for buffet lunch is done according to demand. The analysis of material needs in hotels is very important in the sustainability of food procurement